2018
DOI: 10.1007/s12325-018-0838-2
|View full text |Cite
|
Sign up to set email alerts
|

Earlier Versus Later Augmentation with an Antipsychotic Medication in Patients with Major Depressive Disorder Demonstrating Inadequate Efficacy in Response to Antidepressants: A Retrospective Analysis of US Claims Data

Abstract: IntroductionThere is little evidence regarding the most effective timing of augmentation of antidepressants (AD) with antipsychotics (AP) in patients with major depressive disorder (MDD) who inadequately respond to first-line AD (inadequate responders). The study’s objective was to understand the association between timing of augmentation of AD with AP and overall healthcare costs in inadequate responders.MethodsUsing the Truven Health MarketScan® Medicaid, Commercial, and Medicare Supplemental databases (7/1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Multiple meta-analysis studies from published clinical trials (up until 2010) also show that the use of adjunctive AAPs was significantly more effective than placebo or antidepressant therapy alone in terms of achieving remission or clinical response 1821. Use of adjunctive AAP in patients with MDD also shows significant reductions in all-cause, and MDD-related hospitalizations and ED visits despite increases in pharmacy fills and physician office visits,22 and early treatment – within the first year of first antidepressant therapy or within six months of evidence of inadequate therapy – is associated with significantly lower all-cause cost23 and greater reduction in hospitalization and overall medical costs22 compared to delayed treatment. Three AAPs, including aripiprazole (2007), extended-release quetiapine (2009), and brexpiprazole (2015), are approved by the FDA as an adjunctive treatment for MDD 24–26.…”
Section: Introductionmentioning
confidence: 95%
“…Multiple meta-analysis studies from published clinical trials (up until 2010) also show that the use of adjunctive AAPs was significantly more effective than placebo or antidepressant therapy alone in terms of achieving remission or clinical response 1821. Use of adjunctive AAP in patients with MDD also shows significant reductions in all-cause, and MDD-related hospitalizations and ED visits despite increases in pharmacy fills and physician office visits,22 and early treatment – within the first year of first antidepressant therapy or within six months of evidence of inadequate therapy – is associated with significantly lower all-cause cost23 and greater reduction in hospitalization and overall medical costs22 compared to delayed treatment. Three AAPs, including aripiprazole (2007), extended-release quetiapine (2009), and brexpiprazole (2015), are approved by the FDA as an adjunctive treatment for MDD 24–26.…”
Section: Introductionmentioning
confidence: 95%
“…It was found that the patients receiving early augmentation had reduced healthcare expenditure. 6 Augmenting pharmacotherapy with cognitive behavior therapy in obsessive-compulsive disorder is found to be more effective in reducing the symptoms severe cases of obsessive-compulsive disorder. 7,8 In most conditions, psychotherapy (eg, cognitive behavior therapy) is introduced early in the course of treatment as an addition to the pharmacotherapy.…”
mentioning
confidence: 99%
“…In a study, patients with major depressive disorder with inadequate response to antidepressants received early augmentation with antipsychotic medications. It was found that the patients receiving early augmentation had reduced healthcare expenditure 6 . Augmenting pharmacotherapy with cognitive behavior therapy in obsessive–compulsive disorder is found to be more effective in reducing the symptoms severe cases of obsessive–compulsive disorder 7 …”
mentioning
confidence: 99%
“…Since that time, their use has greatly expanded, and DRBAs are now used to treat a variety of psychiatric conditions including major depressive disorder, bipolar disorder, and irritability associated with autistic disorder. The importance of DRBA treatment in patients with first-break psychosis 1 and major depressive disorder not responding to first-line antidepressant monotherapy 2 has recently been demonstrated in terms of reduced hospital admissions and health care costs. Early initiation of long-acting injectable DRBA formulations has also garnered significant value by decreasing hospitalizations and overall costs within contemporary international practice models.…”
mentioning
confidence: 99%